2022
DOI: 10.1080/15548627.2022.2138687
|View full text |Cite
|
Sign up to set email alerts
|

The telomeric protein TERF2/TRF2 impairs HMGB1-driven autophagy

Abstract: TERF2/TRF2 is a pleiotropic telomeric protein that plays a crucial role in tumor formation and progression through several telomere-dependent and -independent mechanisms. Here, we uncovered a novel function for this protein in regulating the macroautophagic/autophagic process upon different stimuli. By using both biochemical and cell biology approaches, we found that TERF2 binds to the non-histone chromatin-associated protein HMGB1, and this interaction is functional to the nuclear/cytoplasmic protein localiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…During autophagy, depletion of TERF2 promotes autophagy [57]. Lachettini et al [58] reported that TERF2 knockdown induces autophagy by sequestering HMGB1 into the nucleus, where it exerts its pro-autophagic effect when it is shuttled from the nucleus to the cytosol [59]. Moreover, inhibition of TERF2 leads to autophagic death, and apoptosis has also been proven to occur in gastric cancer [60].…”
Section: -5p Inhibition On Lps-induced Cardiomyocyte Apoptosis and In...mentioning
confidence: 99%
“…During autophagy, depletion of TERF2 promotes autophagy [57]. Lachettini et al [58] reported that TERF2 knockdown induces autophagy by sequestering HMGB1 into the nucleus, where it exerts its pro-autophagic effect when it is shuttled from the nucleus to the cytosol [59]. Moreover, inhibition of TERF2 leads to autophagic death, and apoptosis has also been proven to occur in gastric cancer [60].…”
Section: -5p Inhibition On Lps-induced Cardiomyocyte Apoptosis and In...mentioning
confidence: 99%
“…This suggests that the downregulation of TERF2/TRF2 expression results in telomere uncapping, which plays a crucial role in pregnancy loss (66). Other studies have demonstrated that TERF2 can regulate autophagy by binding to High Mobility Group Box 1 (HMGB1), a non-histone Chromatin-related protein (67). In recent years, a large number of studies have suggested that abnormalities in autophagy may be associated with SA by modulating decidualization, trophoblast cells, and immune cells at the maternal fetal interface (68).…”
Section: A B Cmentioning
confidence: 99%
“…The high mobility group box 1 protein (HMGB1), expressed ubiquitously in the nucleus of almost all eukaryotic cells, interacts with nucleosomes, transcription factors, and histones to regulate DNA replication, repair, recombination, and transcription. 31 After phosphorylation and acetylation, HMGB1 is translocated into the cytosol 32 and subsequently secreted into the intercellular space as an inflammatory cytokine mediator. 33 HMGB1 has been shown to be associated with the activation of cancer-related transcription factors p53, p73, and NF-κB in the nucleus, promoting the invasion of cancer cells.…”
Section: Introductionmentioning
confidence: 99%